Surface functionalization of upconversion nanoparticles using visible light-mediated polymerization. (29th August 2018) - Bagheri, Ali; Sadrearhami, Zahra; Adnan, Nik Nik M.; Boyer, Cyrille; Lim, May
Abstract: Lanthanide-doped upconversion nanoparticles (UCNPs) have unique photoluminescent properties which are useful in many biomedical applications. However, to extend their practical use prior surface modification is essential. Herein, we present a straightforward and generic visible light-mediated method for growing a polymer shell with controlled architecture from the UCNPs surfaces (i.e. "grafting from") and demonstrate an application in the delivery of nitric oxide (NO). Our approach has the advantage that no external photocatalyst or initiator is required to initiate the polymerization of the polymer chains. A silica layer was initially generated on the surfaces of the UCNPs as a platform for tethering 4-cyano-4-((dodecylsulfanylthiocarbonyl) sulfanyl) pentanoic acid (CDTPA), a chain transfer agent. The polymerization of functional monomers (glycidyl methacrylate (GMA), poly(oligo(ethylene glycol) methyl ether methacrylate) (POEGMA) or hydroxyethyl methacrylate (HEMA) were then initiated using CDTPA as initiator/chain transfer agent under blue (460 nm, 0.7 mW/cm 2 ) or green (530 nm, 0.7 mW/cm 2 ) light. The PGMA layer can be used to chemically attach various functional molecules onto the UCNPs surface without affecting the luminescence properties of the particles. The polymers also improve the colloidal stability of the UCNPs in water and biocompatibility of the UCNPs. These particles were then used to store and release NO by functionalizing their surfaces with N -diazeniumdiolates (NONOate) moieties. Using the NONOate functionalized UCNPs, relatively slow and controlled release of NO over 6 h can achieved. Graphical abstract: Image 1 Highlights: Photocatalyst/initiator-free photo-RAFT polymerization. Grafting from strategy to grow polymer chains from the UCNPs surfaces. N-diazeniumdiolates (NONOate) groups were then conjugated to the UCNPs surfaces. These NONOate compounds were utilized for the controlled release of Nitric Oxide.